Fungal lignin peroxidase does not produce the veratryl alcohol cation radical as a diffusible ligninolytic oxidant - Houtman, Carl J. (J Biol Chem, 2018)
Peroxidases are considered essential agents of lignin degradation by white-rot basidiomycetes. However, low-molecular-weight oxidants likely have a primary role in lignin breakdown because many of these fungi delignify wood before its porosity has sufficiently increased for enzymes to infiltrate. It has been proposed that lignin peroxidases (LPs, EC 1.11.1.14) fulfill this role by oxidizing the secreted fungal metabolite veratryl alcohol (VA) to its aryl cation radical (VA(+•)), releasing it to act as a one-electron lignin oxidant within woody plant cell walls. Here, we attached the fluorescent oxidant sensor BODIPY 581/591 throughout beads with a nominal porosity of 6 kDa and assessed whether peroxidase-generated aryl cation radical systems could oxidize the beads. As positive control, we used the 1,2,4,5-tetramethoxybenzene (TMB) cation radical, generated from TMB by horseradish peroxidase. This control oxidized the beads to depths that increased with the amount of oxidant supplied, ultimately resulting in completely oxidized beads. A reaction–diffusion computer model yielded oxidation profiles that were within the 95% confidence intervals for the data. By contrast, bead oxidation caused by VA and the LPA isozyme of Phanerochaete chrysosporium was confined to a shallow shell of LP-accessible volume at the bead surface, regardless of how much oxidant was supplied. This finding contrasted with the modeling results, which showed that if the LP/VA system were to release VA(+•), it would oxidize the bead interiors. We conclude that LPA releases insignificant quantities of VA(+•) and that a different mechanism produces small ligninolytic oxidants during white rot.